Hubungan Dinamika Kelompok Tani Dengan Adopsi Good Tobacco Practices (GTP) Tembakau Voor-Oogst Kasturi - Surya Aditya Wicaksono; Sri Subekti; Sofia Sofia (University of Jember, 2017)
Kasturi voor-oogst tobacco is one of the commodities most widely grown in Jember Regency, by which the productivity is relatively low. Cultivation of kasturi voor-oogst tobacco used the technology package of tobacco practices (GTP). The aim of the research was to know: the relationship between the group dynamics and adoption of GTP of Kasturi voor-oogst tobacco. The research used descriptive and correlational methode, with the proporsionate stratified random sampling. The data were collected by using interviews, observation and documents study. The result of the research showed that there was a real relationship between the group dynamics and adoption of GTP of kasturi voor-oogst tobacco. The group dynamic can make the proces adoption of GTP easier. The better the group dynamics the easier the proces of GTP adoption.